ENHANCED ELECTROCHEMICAL PERFORMANCE OF LITHIUM-ION BATTERIES THROUGH CONSTRUCTION OF MICRO-/NANOSTRUCTURED ANODE CO3O4 - Aloina, Ridha
The increasing need for high-performance lithium-ion batteries and greater energy density, especially for application in electric vehicles and portable electronic devices, surely presents research challenges for designing alternative battery electrode materials. Along with the development of the cathode component of the battery, synergistic improvement of the anode component surely becomes important. A feasible approach to addressing these concerns is to utilize alternative materials such as transition metal oxides which have a theoretical specific capacity greater than 600 mAh g-1 or about two times greater than capacity delivered by conventional anodes such as graphite and LTO. However, the operation of transition metal oxides as anode active materials has encountered problems such as changes in the volume of anode structures that can damage the structure itself, and induce the formation of SEI (solid- electrolyte interface) continuously, impacting battery failure. Therefore, many studies have attempted to improve the performance of transition metal oxide-based anodes by designing appropriate precise morphology or structure, including the synthesis protocol used. Cobalt oxide (Co3O4) is one of the alternative anode candidates with a theoretical capacity of ~890 mAh g-1, which has been widely studied in the last decade. The main topic of this literature review is the morphological control of MOFs-derived cobalt oxide particles as anode active material to improve lithium-ion battery performance, in a research article published in the range 2012?2021. The results showed the achievement in the increase of structural stability performance and reversible capacity of the anode, making the utilization of cobalt oxide (Co3O4) as an alternative anode to the next-generation lithium-ion battery becomes more feasible. As well, in this study the polymorph cobalt-based MOFs-71 with rod-like and plate- like structure has been synthesized to be utilized as a pseudomorph precursor to Co3O4, with diffractograms of PXRD characterization results showed both samples have peak patterns corresponding to references.